Energy Usage Monitoring System With Automatic Tariff Calculation - Hamdzah, Tun Khairul Firdaus Tun (Universiti Sains Malaysia, 2017)
The objective of this project is to design a system that will allow real-time electrical energy usage monitoring with automated tariff calculation and IoT capability. This project uses a microcontroller as the main processor to collect data and perform calculation to get real power (P), apparent power (S) and reactive power (Q) and others. Values of RMS current, RMS voltage, Real Power, Apparent Power, Power Factor and Tariff that have been calculated will be sent to the cloud or an internet server. Users will be able to monitor their real-time power usage online using any internet connected gadgets. A warning or alert message will be sent to the users if their power usage exceeded certain threshold that have been set. This notification message will be sent through the user’s Twitter account to alert the user.